PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKn DENGAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DI KELAS IV SD - BUDIMAN`, ARIF (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study aims to describe the increase in student learning outcomes in learning civics with type TGT cooperative model in the fourth grade. Research that has been conducted shows an increase in the learning process and assessment of student learning outcomes. The experiment was conducted two cycles with RPP assessment results in the first cycle 75% increase in cycle II 96%, and valuation aspects of teacher first cycle 71% increase in cycle II 96%, while the valuation aspects of students' first cycle 68% increase in cycle II 93%. Learning outcomes in the first cycle 63% increase in the second cycle to 80%. So TGT cooperative models can improve learning outcomes Civic Educations Subject.   Kata Kunci: hasil belajar ; pkn;  tipe tgt